2022
DOI: 10.1108/itp-07-2021-0536
|View full text |Cite
|
Sign up to set email alerts
|

Exploring smart retailing: anthropomorphism in voice shopping of smart speaker

Abstract: PurposeThe purpose of this paper is to investigate the effects of anthropomorphism and identify factors related to adopting voice shopping on smart speakers.Design/methodology/approachProgress in partial least squares structural equation modeling (PLS-SEM) approach is used to test the proposed research framework regarding anthropomorphism and user perceptions on voice shopping via smart speakers. Individuals' responses to questions about attitude and intention to use voice shopping via smart speakers were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…Additionally, a "negativity bias" (Park, 2015;Zhu et al, 2020) has been discussed, indicating that negative news might disproportionately affect public sentiment. Similarly, research relying on the privacy-satisfaction model supports the notion that greater feelings of privacy lead to increased user satisfaction (Jang et al, 2022;Lee et al, 2020). Applied to our context, this suggests that the preponderance of negative news about VAPA privacy can deteriorate public sentiment, which is equated with user satisfaction.…”
Section: 3research Questionssupporting
confidence: 71%
See 1 more Smart Citation
“…Additionally, a "negativity bias" (Park, 2015;Zhu et al, 2020) has been discussed, indicating that negative news might disproportionately affect public sentiment. Similarly, research relying on the privacy-satisfaction model supports the notion that greater feelings of privacy lead to increased user satisfaction (Jang et al, 2022;Lee et al, 2020). Applied to our context, this suggests that the preponderance of negative news about VAPA privacy can deteriorate public sentiment, which is equated with user satisfaction.…”
Section: 3research Questionssupporting
confidence: 71%
“…In fact, the more the users interact with VAPAs, the greater they engage with them (Chen et al, 2022). Besides, as Jang et al (2022) recall, the anthropomorphism of VAPAs does not only provide interactivity with the customer but also helps to customize the search process, what can facilitate voice shopping, increasing customer satisfaction and opinions towards smart speakers.…”
Section: Introductionmentioning
confidence: 99%
“…Current e-commerce research leverages advanced technologies such as augmented reality [ 26 , 27 ], electronic word-of-mouth (eWOM), review analysis, social media [ 28 , 29 , 30 , 31 ], haptic sensations, and voice shopping [ 3 , 32 , 33 ]. These technologies have been harnessed to enhance user engagement and personalize the shopping experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The burgeoning e-commerce landscape has positioned the study of consumer behavior in online transactions at the forefront of critical research. Prior investigations have spotlighted elements such as technology [ 1 , 2 , 3 , 4 , 5 , 6 ], trust [ 7 , 8 , 9 ], and convenience [ 10 , 11 , 12 ] as pivotal determinants of consumer behavior. However, the full picture remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the uncanny effect, most research still indicates that a higher level of anthropomorphism can trigger positive feelings about AI [56]. For example, Jang et al identified that anthropomorphism had a positive effect on satisfaction for voice shopping via smart speaker [57]. To go further step, due to the humanoid features of AI anchors, such as unique names, avatars, and hosting styles, users may get induced to the characters exhibited by AI news anchors, thus forming a stronger willingness to continue watching.…”
Section: Perceived Anthropomorphismmentioning
confidence: 99%